The Protective Effect of Docosahexaenoic Acid on Mitochondria in SH-SY5Y Model of Rotenone-Induced Toxicity - Britta Eggers; Jennifer Stepien; Anne-Katrin Reker; Svenja Esser; Kathy Pfeiffer; Magdalena Pawlas; Katalin Barkovits; Katrin Marcus (Metabolites)
Background: Polyunsaturated fatty acids in particular omega-3 fatty acids, such as docosahexaenoic acid (DHA), are essential nutrients and components of the plasma membrane. They are involved in various processes, including synaptic development, functionality, integrity, and plasticity, and are therefore thought to have general neuroprotective properties. Considerable research evidence further supports the beneficial effects of omega-3 fatty acids, specifically on mitochondria, through their antioxidant and anti-apoptotic properties, making them an attractive addition in treatment options for neurodegenerative disorders in which mitochondrial alterations are commonly observed. However, precise information on the underlying protective mechanisms is still lacking. Methods: We utilized the most common neuronal cell line (SH-SY5Y) and induced mitochondrial oxidative stress through the addition of rotenone. To study the potential protective effect of DHA, the cells were additionally pre-treated with DHA prior to rotenone administration. By combining SILAC labeling, mitochondria enrichment, and subsequent proteomic analyses, we aimed to determine the capacity of DHA to alleviate mitochondrial oxidative stress in vitro and further shed light on the molecular mechanisms contributing to the proposed neuroprotective effect. Results: We confirmed a reduced cell viability and an increased abundance of reactive oxygen species upon rotenone treatment, DHA pre-treatment was shown to decrease said species. Additionally proteomic analysis revealed an increased expression of mitochondrial proteins in DHA pre-treated cells. Conclusions: With our study, we were able to define a potential compensatory mechanism by which the inhibition of complex I is overcome by an increased activity of the fatty acid beta oxidation in response to DHA.